Growth and yield of colored-fiber cotton grown under salt stress and nitrogen fertilization - Geovani S. de Lima; Adaan S. Dias; Lauriane A. dos A. Soares; Hans R. Gheyi; Reginaldo G. Nobre; Leandro de P. Souza (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This research was conducted in order to evaluate the growth and production of colored-fiber cotton, cv. ‘BRS Rubi’, irrigated with water of different salinities and nitrogen (N) doses. The experiment was carried out in drainage lysimeters filled with soil material from an eutrophic Regolithic Neosol with sandy-loam texture under greenhouse conditions in Campina Grande, PB. The experiment was conducted in a randomized block design and the treatments consisted of five levels of irrigation water salinity with the following electrical conductivities - ECw (5.1, 6.1, 7.1, 8.1 and 9.1 dS m-1), combined with five N doses - ND (65; 100; 135; 170; 205 mg of N kg-1 of soil), distributed in a 5 x 5 factorial scheme with three replicates. The growth of the cotton cv. ‘BRS Rubi’ was negatively affected by irrigation with saline water, and the leaf area was the most sensitive variable; the highest production of seed cotton and number of bolls per plant were obtained using water of 5.1 dS m-1 and N dose of 170 mg kg-1.